The number of donor HLA-derived T cell epitopes available for indirect antigen presentation determines the risk for vascular rejection after kidney transplantation - Betjes, Michiel G. H.; Peereboom, Emma T. M.; Otten, Henny G.; Spierings, Eric (Frontiers in Immunology, 2022)
The role of the indirect T-cell recognition pathway of allorecognition in acute T cell-mediated rejection (aTCMR) is not well defined. The amount of theoretical T-cell epitopes available for indirect allorecognition can be quantified for donor-recipient combinations by the Predicted Indirectly ReCognizable HLA Epitopes algorithm (PIRCHE-II). The PIRCHE-II score was calculated for 688 donor kidney-recipient combinations and associated with the incidence of first-time diagnosed cases of TCMR. A diagnosis of TCMR was made in 182 cases; 121 cases of tubulo-interstitial rejection cases (79 cases of borderline TCMR, 42 cases of TCMR IA-B) and 61 cases of vascular TCMR (TCMR II-III). The PIRCHE-II score for donor HLA-DR/DQ (PIRCHE-II DR/DQ) was highly associated with vascular rejection. At one year after transplantation, the cumulative percentage of recipients with a vascular rejection was 12.7%, 8.6% and 2.1% within respectively the high, medium and low tertile of the PIRCHE-II DR/DQ score (p<0.001). In a multivariate regression analysis this association remained significant (p<0.001 for PIRCHE-II DR/DQ tertiles). The impact of a high PIRCHE-II DR/DQ score was mitigated by older recipient age and a living donor kidney. In conclusion, indirect antigen presentation of donor HLA-peptides may significantly contribute to the risk for acute vascular rejection.